2013
DOI: 10.18097/pbmc20135904452
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in the of alcoholic liver disease

Abstract: 1Федеральное Государственное бюджетное учреждение "Научно-исследовательский институт общей патологии и патофизиологии" Российской академии медицинских наук, Москва 2 Федеральное Государственное бюджетное учреждение "Национальный Научный центр наркологии" Министерства здравоохранения РФ, 119002, Москва, Мал. Могильцевский пер., 3; тел.: +7 499 2419446; факс: +7 499 2419590; эл. почта: boris.davidov2@yandex.ru 3 Федеральное Государственное бюджетное образовательное учреждение высшего профессионального образовани… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
4
0
3
Order By: Relevance
“…HBV-, HCV- and alcohol- triggered oxidative stress and induce liver damage[45]. It could be of therapeutic value in protecting the liver from injury, inflammation, and carcinogenesis [4651]. There are several possible agents for preventing stress related liver pathogenesis, such as curcumin [52, 53], silymarin [54], green tea [55], and vitamins C or E [56].…”
Section: Discussionmentioning
confidence: 99%
“…HBV-, HCV- and alcohol- triggered oxidative stress and induce liver damage[45]. It could be of therapeutic value in protecting the liver from injury, inflammation, and carcinogenesis [4651]. There are several possible agents for preventing stress related liver pathogenesis, such as curcumin [52, 53], silymarin [54], green tea [55], and vitamins C or E [56].…”
Section: Discussionmentioning
confidence: 99%
“…The infiltration of inflammatory cells, activation of macrophage, and the proinflammatory mediators like LPS, TNF- α , IL1 β , and IL6 induced by various pathways, such as alcohol-regulated CD14/Toll-like receptor 4 (TLR4) pathway, could provoke cellular injury and apoptosis, resulting in ALD [18, 19]. The activation of KCs by lipopolysaccharides (LPS) via TLR4 is critical to the onset of alcohol-induced hepatic damage, which could enhance the production of inflammatory cytokines and ROS which contribute to ALD [31, 49, 50]. MicroRNA-155, an important regulator of inflammation, has been demonstrated to play a vital role in alcohol-induced steatohepatitis and fibrosis.…”
Section: The Relationship and Interdependence Between Oxidative Stmentioning
confidence: 99%
“…It has been reported that in alcoholic patients oxidative stress contributes strongly to forming somatic complications [ 64 ], disturbance of immune status [ 65 ], and induction of apoptosis [ 66 ]. In alcoholism, formation of OS can be increased by ethanol, the concentration of which significantly exceeds the norm in patients, as well as the toxic metabolite of ethanol-acetaldehyde, whose level also increases in the organism during alcoholic intoxication.…”
Section: Correction Of Oxidative Stress With Carnosine In Alcoholimentioning
confidence: 99%